Voice characteristics of people with Parkinsons disease (PwP): An overview on baseline vocal characteristics and guidelines for therapeutic singing - Ang, Mei Foong (Universiti Pendidikan Sultan Idris, 2018)
Parkinson’s Disease (PD) is a chronic neurodegenerative disease in which the symptoms of the disease are worsen over time. Core symptoms of the disease are such as tremor-at-rest, rigidity, postural instability, and bradykinesia. Apart from these motor-problems, other problems such as sleep disorder, sensory abnormalities, neuropsychiatric disorders also exist. In addition to the motor-problems, latest literature documented 80-90% of the people with Parkinson’s Disease (PwP) are prone to develop voice impairment known as Parkinsonian Dysarthria, when symptoms deteriorate, causing loss of communication, difficulties in swallowing and breathing that are psychologically devastating and life threatening. Growing research in music therapy (MT) and music-based rehabilitative activities worldwide documented positive effects on PwP. A local research using therapeutic singing as rehabilitative model at the Malaysian Parkinson’s Disease Association (MPDA) also have reported positive benefits in improving vocal problems in the Malaysian PwP. In this research, some primary and preliminary data on the vocal characteristic, including baseline vocal loudness (VL), pitch range (PR) and respiratory rate (RR) were obtained among 22 local PwP prior to examining effects of singing on PwP. Findings of this study showed that the PwP speak softer than the normal accepted range. The findings also showed that they have tendency to develop rapid breathing, and their average pitch range while singing is limited within the range of G#3 – B4. These findings can further propose guidelines for voice rehabilitation models based on the preliminary voice characteristics concluded in this study.